Study of the Relationship between Burnout and Resilience among Nurses at the Outbreak of COVID-19 - Farzaneh Fouladi; Masoumeh Fouladi (Tehran University of Medical Sciences, 2021)
Background: Covid-19 pandemic peak put additional strains on healthcare system. In this crisis, the resilience of nursing staff is critical. This study aimed to investigate the relationship between burnout and resilience in frontline nursing staff working in high-risk areas during the outbreak of Covid-19 pandemic. Materials and Methods: The present study is a Descriptive-analytical survey, and the target group is Iranian nurses. According to the Ministry of Health statistics, 125369 people are participated in this study. information is collected from 384 people by cluster distribution using questionnaire. The statistical analysis in this study is performed by SPSS and SMART-PLS software Results: According to the study, all the collected information is normal. Based on factor analysis, there is an inverse significant relationship between resilience and burnout, and also, the sense of success has a significant effect on resilience as part of burnout. Conclusion: In order to increase the resilience of nursing staff in such conditions, it is necessary to pay more attention to the factors affecting their burnout and plan to minimize it. Developing educational programs and adding diversity in service delivery might be useful to enhance personal feelings and also reduce burnout.